Hubungan Antara Frekuensi Makan Dengan Status Gizi Balita - Rendita Dwibarto (Institut Citra Internasional, 2023)
The success of the nutrition program, 30% is determined by the health or nutrition sector which is called specific interventions and 70% by the external health sector which is called sensitive intervention. Data on the nutritional status of toddlers in the 2017 Pundong Health Center area, malnutrition status in Selorejo Village was 9.7%, Panjang Rejo was 7.3% and Srihardono Village was 13.7%. The cause of malnutrition problems at the Tangkil Posyandu is caused by many factors, one of which is the lack of attention from parents to provide breast milk and food for their children because the child is entrusted to his grandmother and the mother works. The purpose of this study was to determine the relationship between eating frequency and nutritional status of toddlers aged 6 months to 60 months in Pundong District, Srihardono Village, Tangkil Hamlet. This type of research is a quantitative study with a cross sectional design. The research population is 36 respondents. The sampling technique is a saturated sample. The sample of this research is 36 respondents. Statistical test using the Chi-Square Test. The research tool is a questionnaire. The results of the analysis based on the results of the Chi-Square Test showed that the value of p (0.000) <0.05 means that the frequency of eating is related to nutritional status.